O cisne noutros lugares ou Da impossibilidade de esquecer a dor - Amorim, Orlando Nunes de [UNESP] (My University, 2013)
Taking into consideration the previous critical interpretations about Baudelaire’s poem called “Le cygne” (Benjamin, Oehler, Barbosa), this article highlights some relevant aspects about allegorical structure, seeking to demonstrate how the feeling of exile and the melancholy, which define the poetic individual and which represent underlying themes in Baudelaire’s poem, can be read through a frame of reference which links both historical-political and psychoanalytical interpretations.

Partindo de leituras e interpretações já consagradas do poema “Le cygne”, de Baudelaire (Benjamin, Oehler, Barbosa), este artigo busca destacar certos aspectos relevantes da sua estrutura alegórica, procurando demonstrar como o sentimento de exílio e a melancolia característica do sujeito poético, temas fundacionais do poema baudelairiano, podem ser lidos numa perspectiva intermediária entre a interpretação histórico-política e a psicanalítica.
The swan in other places or About the impossibility to forget pain
Keywords: Alegoria; Charles Baudelaire; Exílio; Melancolia; Allegory; Charles Baudelaire; Exile; Melancholy